Geological Storage of CO2 - Long Term Security Aspects GEOTECHNOLOGIEN Science Report No. 22 - Liebscher, Axel; Münch, Ute (Advanced Technologies in Earth Sciences,, 2015)
This book explores the industrial use of secure, permanent storage technologies for carbon dioxide (CO2), especially geological CO2 storage. Readers are invited to discover how this greenhouse gas could be spared from permanent release into the atmosphere through storage in deep rock formations. Themes explored here include CO2 reservoir management, caprock formation, bio-chemical processes and fluid migration. Particular attention is given to groundwater protection, the improvement of sensor technology, borehole seals and cement quality. A collaborative work by scientists and industrial partners, this volume presents original research, it investigates several aspects of innovative technologies for medium-term use and it includes a detailed risk analysis. Coal-based power generation, energy consuming industrial processes (such as steel and cement) and the burning of biomass all result in carbon dioxide. Those involved in such industries who are considering geological storage of CO2, as well as earth scientists and engineers will value this book and the innovative monitoring methods described. Researchers in the field of computer imaging and pattern recognition will also find something of interest in these chapters.